Low-carbon binders and building materials that provide summer comfort

JP7943651B2Active Publication Date: 2026-10-30MATERRUP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023544351
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-12
Filing Date
2022-01-19
Publication Date
2026-10-30
Estimated Expiration
2042-01-19

AI Technical Summary

Benefits of technology

によれば、掘削された土は、生産現場又は200km未満、好ましくは50km未満の距離で使用される。さらに、有利には、本発明に関連して掘削された粘土は、未処理の掘削された粘土、すなわち焼成工程を経ていないものである。特に、事前の熱処理は一切受けていないことを意味する。例えば、これは、300℃を超える、好ましくは200℃を超える、より好ましくは150℃を超える温度上昇を受けていない粘土質土壌に相当する。実際、原料粘土土壌は、一般に実質的に150℃に等しい温度上昇を必要とする加熱ステップを受けることができるが、焼成ステップは必要ない。焼成ステップは、例えば、600℃を超える温度で少なくとも1時間の熱処理に相当し得る。従来使用されている粘土は、サイズが2μm未満で比較的一定した粒度プロファイルを持っている。掘削された粘土土壌は、異なる粒度プロファイルを持つ場合がある。本発明の文脈において、掘削された粘土土壌は、規格ASTMD422-63に従って測定した場合、2μmを超える、好ましくは20μmを超える、好ましくは50μmを超える、例えば75μmを超えるサイズの粒子を含み得る。好ましくは、掘削された粘土土壌は、規格NF EN933-1に従って決定されるように2cmを超える顆粒を含まない。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943651000007
    Figure 0007943651000007
  • Figure 0007943651000001
    Figure 0007943651000001
  • Figure 0007943651000002
    Figure 0007943651000002
Patent Text Reader

Abstract

The present invention relates to a method (100) for producing a prefabricated element, as well as a building binder comprising a raw clay matrix, a deagglomerating agent and an activating composition, wherein: the raw clay matrix comprises at least one raw clay from the smectite group; at least one raw clay from the smectite group represents at least 20% by weight of said construction binder, The building binder contains less than 15% by weight of Portland cement.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to the field of building materials, and more particularly to the field of binders that can be used in construction. This invention relates to formulations of building binders. This invention also relates to methods for manufacturing building binders, building binders themselves, and the use of such binders in the manufacture of building materials. Building materials thus obtained are also the subject of this invention and provide summer comfort (e.g., passive humidity regulation) to buildings incorporating them. [Background technology]

[0002] Cement is the world's second-largest resource in terms of consumption, with over 4 billion tons produced globally each year. This consumption is constantly increasing due to growing demand for housing and infrastructure.

[0003] Cement is generally a hydraulic binder that hardens and solidifies when mixed with water. After hardening, cement retains its strength and stability even when exposed to water. A wide variety of cements are used worldwide. However, all conventional cements contain clinker in proportions ranging from 5% in certain blast furnace cements to at least 95% in Portland cement, the most widely used cement in the world today.

[0004] Clinker is produced by firing a mixture consisting of approximately 80% limestone and 20% aluminosilicate (such as clay). This firing, or clinking, generally takes place at temperatures exceeding 1200°C, making such cement preparation processes highly energy-intensive. Furthermore, carbon dioxide is released when limestone is chemically converted into lime. As a result, the cement industry accounts for approximately 8% of global CO2 emissions. Faced with this challenge, the industry and researchers are exploring possibilities to mitigate the impact of carbon dioxide emissions generated by the cement industry.

[0005] To reduce carbon dioxide emissions related to the construction sector, a novel low-carbon building binder formulation containing a raw clay matrix and an anti-flocculation agent has been proposed (International Publication No. 2020 / 141285). However, this document mainly describes the use of compositions that can reduce carbon dioxide emissions as building materials while possessing high mechanical strength. A method for selecting the composition of a building material including excavated clay (International Publication No. 2020178538) or a binder (French Patent Application Publication No. 3084357) containing at least one raw clay capable of achieving the necessary performance for tensile adhesion of tile adhesives has also been proposed.

[0006] In addition to reducing carbon emissions, consumers could benefit from alternatives to Portland cement that possess humid properties that can provide comfort to residents during hot weather.

[0007] The extensive use of air conditioning, heating, and other air recycling and ventilation systems to control temperature and humidity levels within a building results in significant CO2 emissions (both during manufacturing and throughout use). In contrast, passive control of temperature or humidity levels consumes no energy and requires no human monitoring. Therefore, in many situations where energy consumption of heat, humidity, or more generally ventilation control systems can be reduced, it becomes a more resilient and sustainable option.

[0008] However, this aspect is not currently being studied in the construction industry, and the rare materials recognized as having moist heat properties that can provide comfort in summer are less industrialized building materials, based on bio-resource products such as wood (chips, fibers), hemp (hemp sieves), and straw, or geographical resources such as earth-derived materials (rammed earth, clay bricks, coblets, etc.).

[0009] In particular, using hemp in the manufacture of mortar, coatings, and prefabricated hemp concrete elements provides highly satisfactory thermal insulation properties, optimal humidity control, and a very interesting carbon balance in its production. On the other hand, bio-based building materials very often have relatively weak mechanical properties, limiting their use to insulation, coatings, or the formation of wall partitions where little mechanical stress is applied. Furthermore, the relatively long drying time of hemp concrete (e.g., more than 5 days) further restricts its use.

[0010] Therefore, there is a demand for novel fast-setting building binder formulations that, on the one hand, have low carbon dioxide emissions and possess mechanical properties at least equivalent to or better than those of concrete obtained from cement commonly used in the construction sector (cement CEM I, CEM II, CEM III, CEM IV, CEM V, etc. as defined in standard NF EN197-1), and on the other hand, enable passive control of temperature and humidity in buildings incorporating such building binders. [Overview of the project] [Problems that the invention aims to solve]

[0011] The objective of this invention is to overcome the shortcomings of the prior art. In particular, the objective of this invention is to propose a building binder that enables the creation of building materials that can regulate temperature and humidity while maintaining mechanical properties that are suitable for the constraints of modern architecture. Furthermore, the objective of this invention is to provide a material that also has rapid curing properties for specific applications.

[0012] Furthermore, an object of the present invention is to provide a method for manufacturing a building binder that can reduce the emission of greenhouse gases such as carbon dioxide emitted during the manufacture of building materials, while simultaneously maintaining the appropriate mechanical properties of the said materials and providing moist heat control properties. [Means for solving the problem]

[0013] To achieve this object, the inventors have developed several solutions that can address the drawbacks of the prior art. Preferred solutions are described in detail below.

[0014] The present invention particularly relates to a construction binder comprising a raw clay matrix, an anti-agglomeration agent and an activation composition, characterized by the following features. · The raw clay matrix comprises at least one raw clay from the smectite group, · The at least one raw clay from the smectite group accounts for at least 20% by weight of the construction binder, · The construction binder comprises less than 15% by weight of Portland cement.

[0015] In particular, the present invention relates to a construction binder comprising a raw clay matrix, an anti-agglomeration agent and an alkaline activation composition, characterized by the following features. · Comprising 2% to 40% by dry weight of the alkaline activation composition, · Comprising at least 40% by weight of the raw clay matrix, wherein the raw clay matrix comprises at least one raw clay from the smectite group; and the at least one raw clay from the smectite group accounts for at least 20% by weight of the construction binder; · The construction binder comprises less than 15% by weight of Portland cement.

[0016] As shown in the examples, the construction binder according to the present invention provides moisture buffering capacity that can improve occupant comfort through thermal and humidity regulation. Furthermore, the construction binder according to the present invention is intended to replace Portland cement in whole or in part, thanks to the combination of its mechanical properties and its thermal and moisture regulation properties. In fact, the present inventors have shown that the presence of smectite at at least a predetermined concentration in the construction binder according to the present invention makes it possible to achieve very good moisture buffering capacity values. Under these conditions, this cannot be achieved with other raw clays such as kaolinite alone.

[0017] Furthermore, as shown below, the building binder achieves mechanical performance equivalent to Portland cement (e.g., Class C12 / 15, C20 / 25, or C25 / 30) while reducing greenhouse gas emissions by 30-85%, and provides comfort to occupants through temperature and humidity regulation. Moreover, it contains little to no Portland cement. In fact, as shown in the examples, the presence of Portland cement leads to a decrease in moisture buffering capacity.

[0018] Depending on any other properties of the building binder, the building binder may optionally include one or more of the following properties, either individually or in combination: The raw clay matrix comprises a mixture of at least two types of clay. Preferably, the raw clay matrix comprises at least one raw clay from the smectite family and at least one other clay selected from the following: illite; kaolinite; vermiculite; chlorite; muscovite; halloysite; sepiolite or attapulgite. In fact, as shown in the examples, combining clays yields better results in terms of moisture buffering capacity and mechanical resistance. • The raw clay matrix is ​​measured according to standard NFP94-068, for example, and is at least 100 m 2 Specific surface area equal to / g, at least 150m² 2 Specific surface area equal to / g, at least 200m² 2 A specific surface area equal to / g, or at least 250m² 2 It contains at least one clay having a specific surface area equal to / g. More preferably, the raw clay matrix has at least 100m 2 / g, at least 150m 2 Specific surface area equal to / g, at least 200m² 2 A specific surface area equal to / g, or at least 250m² 2 It contains at least two clays having a specific surface area equal to / g. Preferably, the specific surface area can be measured using the protocol described in standard NFP94-068, NF EN933-9+A1, or ISO9277:2010. More preferably, the building binder contains at least 20% by weight, and more preferably less than 40% by weight, of clays having such a specific surface area. The binder contains at least 10% by weight, preferably at least 30% by weight, and more preferably at least 40% by weight of raw clay matrix. In fact, as shown in the examples, a building binder from at least 40% by weight of raw clay matrix enables the preparation of building materials having a moisture buffer capacity (MBV) of 1.3 or higher. For example, the raw clay matrix can be present in an amount of 40% to 70% by weight, preferably 40% to 60% by weight, of the building binder. The material further comprises a calcined metal oxide composition. Preferably, the calcined metal oxide composition is blast furnace slag. In fact, as shown in the examples, unlike Portland cement, the calcined metal oxide composition can increase mechanical strength without affecting the MBV. Preferably, the building binder contains at least 20% by weight of the calcined metal oxide composition. More preferably, the mass ratio of the raw clay matrix to the calcined metal oxide composition is 1 or more. The activation composition contains at least 40% by weight of at least one metal oxide corresponding to an oxide of a metal having at least two valence electrons. In particular, the activation composition may contain at least 50% by weight of a metal oxide corresponding to an oxide of a metal having at least two valence electrons. The presence of such metal oxides in the activation composition at these concentrations can increase the moisture buffering capacity. The building binder contains at least 10% by weight of at least one metal oxide corresponding to an oxide of a metal having at least two valence electrons. Preferably, at least 10% by weight may correspond to several different metal oxides. Metal oxides formed from metals having at least two valence electrons can be obtained from several sources. Preferably, these metal oxides are included in the activated composition and / or the calcined metal oxide composition. Preferably, the building binder contains at least 15% by weight, more preferably at least 20% by weight, even more preferably at least 25% by weight, for example at least 30% by weight of at least one metal oxide corresponding to an oxide of a metal having at least two valence electrons. The building binder may contain less than 50% by weight of at least one metal oxide corresponding to an oxide of a metal having at least two valence electrons. For example, the building binder may contain between 15% and 40% by weight of at least one metal oxide corresponding to an oxide of a metal having at least two valence electrons. The building binder, a combination of water and granules, has a moisture buffer value of 0.75 or higher, preferably 1 or higher, more preferably 1.2 or higher, and even more preferably 1.5 or higher, measured within 10 days, preferably 28 days, after manufacture. • The anti-coagulant is an organic compound. Preferably, the anti-coagulant includes lignosulfonates, polyacrylates, humicates, or mixtures thereof. • The excavated soil contains at least a portion of the raw clay matrix. The excavated soil can be considered as excavated clay. Furthermore, the composition contains at least 20% by weight of calcined aluminosilicate, or contains at least 20% aluminosilicate in the composition of metal oxides.

[0019] According to another aspect The present invention relates to building materials that can be formed from a building binder according to the present invention, which includes the following: • At least 2% by weight of at least one raw material clay from the smectite family, • Portland cement less than 3.75% by weight; The moisture buffering value measured within 10 days after manufacture is 0.75 or more, preferably 1 or more. The moisture buffering value is measured according to the method for measuring the MBV value described in the specification.

[0020] According to a specific aspect, the present invention also relates to a building material formed from the building binder according to the present invention, comprising at least 2% by weight of at least one raw clay from the smectite family and less than 3.75% by weight of Portland cement.

[0021] According to other optional properties of the building material, the latter may optionally comprise one or more of the following properties, alone or in combination: ·Comprising at least 2% by weight of a calcined metal oxide composition. ·It preferably contains less than 2% Portland cement, more preferably less than 0.1%, and even more preferably contains no Portland cement. ·Comprising at least two raw clays. ·Comprising at least 5% by weight of at least one metal oxide corresponding to an oxide of a metal having at least two valence electrons. ·The minimum compressive strength of the cylinder after 1 day, measured according to standard NF EN206-1, is 2 MPa or more. For example, it may have a minimum compressive strength of 2 MPa or more on the cylinder after 28 days, as measured according to standard NF EN206-1. Furthermore, the minimum compressive strength of the cylinder after 28 days, measured according to standard NF EN206-1, may be 20 MPa or less.

[0022] According to another embodiment , the present invention relates to a prefabricated element that can be formed from the building binder according to the present invention, said prefabricated element: ·Has a surface area of at least 1 m 2 and a thickness of 0.3 cm to 20 cm, ·Comprising at least 5% by weight of at least one raw clay from the smectite family, ·Comprising less than 3.75% by weight of Portland cement, • The moisture buffer value measured within 10 days of manufacture is 0.75 or higher. The moisture buffer value can be measured according to the method for measuring the MBV value described in the specification.

[0023] In certain embodiments, the present invention also relates to a prefabricated element formed from a building binder according to the present invention, wherein the building binder has a surface area of ​​at least 1 m² 2 The surface has a thickness of 0.3 cm to 20 cm, contains at least 5% by weight of at least one raw material clay from the smectite tribe, and contains less than 3.75% by weight of Portland cement.

[0024] According to any other properties of the prefabricated element, the prefabricated element contains at least 2% by weight of a calcined metal oxide composition.

[0025] According to another aspect The present invention relates to a method for manufacturing building materials, comprising the following steps: To provide a building binder comprising a raw clay matrix containing at least one raw clay from the smectite family, an anti-coagulation agent, and an alkaline activating composition (the at least one raw clay from the smectite family constitutes at least 20% by weight of the building binder, and the building binder contains less than 15% by weight of Portland cement); • Add water and granules; and • To obtain building materials by mixing them.

[0026] According to another aspect The present invention relates to a method for producing prefabricated elements prepared from a building binder, wherein the building binder comprises a raw clay matrix, an activating composition, and an anti-flocculating agent, and the method is To provide a building binder comprising a raw clay matrix containing at least one raw clay from the smectite family, an anti-coagulation agent, and an alkaline activating composition (the at least one raw clay from the smectite family constitutes at least 20% by weight of the building binder, and the building binder contains less than 15% by weight of Portland cement); • Mixing the building binder with granules and water; and • Perform a curing step of the mixture (the curing step preferably includes heat-treating the mixture at a temperature of 100°C or lower for a period of 2 to 23 hours).

[0027] In particular, the present invention relates to a method for producing prefabricated elements prepared from a building binder comprising a raw clay matrix, an alkaline activating composition, and an anti-coagulant, wherein the method is To provide a building binder comprising a raw clay matrix containing at least one raw clay from the smectite family, an anti-coagulation agent, and an alkaline activating composition (the building binder contains 2% to 40% by dry weight of the alkaline activating composition, the at least one raw clay from the smectite family corresponds to at least 20% by weight of the building binder, and the building binder contains less than 15% by weight of Portland cement); • Mixing the building binder with granules and water; and • Perform a curing step of the mixture (the curing step preferably includes heat-treating the mixture at a temperature of 100°C or lower for a period of 2 to 23 hours).

[0028] When a building binder is mixed with granules and water, a building material is obtained. This method makes it possible to produce a building material with low carbon dioxide emissions and moisture-buffering capabilities that can improve the comfort of residents by regulating heat and humidity.

[0029] Furthermore, the use of a curing step enables rapid curing, which is suitable for the manufacture of prefabricated elements.

[0030] Furthermore, in some embodiments, these prefabricated elements may have mechanical properties at least equivalent to, or even better than, those of concrete obtained from cement commonly used in the construction field, after a curing time of 23 hours or less.

[0031] Furthermore, by using specific formulations, it becomes possible to obtain building materials that can rapidly harden as required for specific architectural styles.

[0032] therefore, Another aspect According to this, the present invention is formed from, or can be formed from, a building binder according to the present invention. building materials Regarding.

[0033] Depending on any other properties of the building material, the latter may include, individually or in combination, one or more of the following properties: The mixture contains at least 2% by weight, for example, at least 5% by weight, preferably at least 8% by weight, and more preferably at least 10% by weight, of at least one raw material clay from the smectite family. In fact, it has been shown that the presence of smectite or similar clay improves moisture buffering capacity. • Contains less than 3.75% by weight of Portland cement. • Contains at least two raw clay materials. In fact, the presence of a combination of clays has been shown to improve moisture buffering capacity and mechanical resistance. Furthermore, it contains at least 5% by weight of at least one metal oxide corresponding to an oxide of a metal having at least two valence electrons, preferably at least 10% by weight of at least one metal oxide corresponding to an oxide of a metal having at least two valence electrons. This improves moisture buffering capacity and mechanical strength. • Contains diatom shells or plant fibers, preferably hemp sieves. • It has a moisture buffer value of 0.75 or higher, preferably 1 or higher, measured within 10 days of manufacture. The minimum compressive strength on the cylinder after one day, as measured according to standard NF EN206-1, is 2 MPa or higher, preferably 3 MPa or higher, and preferably 5 MPa or higher. Advantageously, the building material has a minimum compressive strength on the cylinder after seven days, as measured according to standard NF EN206-1, of 8 MPa or higher, preferably 10 MPa or higher.

[0034] therefore, Another aspectAccording to this, the present invention can be formed from a building binder according to the present invention, and at least 1 m 2 It has a surface with an area and a thickness of 0.3 cm to 20 cm. Prefabricated elements Regarding.

[0035] Such prefabricated elements are advantageous if their moisture buffer value, measured over 10 days, is 0.75 or higher, preferably 1 or higher, more preferably 1.2 or higher, and even more preferably 1.5 or higher.

[0036] Such prefabricated elements are advantageous in that they contain less than 3.75% by weight of Portland cement.

[0037] Such prefabricated elements are advantageous in that they contain at least 5% by weight of at least one raw material clay from the smectite tribe.

[0038] Such prefabricated elements are particularly well-suited for use in residential buildings. In fact, the combination of a large surface area and high moisture buffering capacity allows for more precise adjustments. Furthermore, the thickness can be selected according to the desired regulatory level.

[0039] Other advantages and features of the present invention will become apparent from reading the following description, which is given as an exemplary and non-limiting example, with reference to Appendix Figure 1, which shows a diagram of a method for manufacturing prefabricated elements produced from the building binder according to the present invention. [Brief explanation of the drawing]

[0040] [Figure 1] This diagram illustrates a method for manufacturing prefabricated elements produced from a building binder according to the present invention. [Modes for carrying out the invention]

[0041] In the remainder of this explanation, the term “weight %” in relation to raw clay matrix, binder, or building material should be understood as a percentage of the dry weight of the binder or building material. Dry weight corresponds, for example, to the weight before the addition of water necessary for forming the building material.

[0042] In the sense of the present invention, the term "dehydrated" corresponds to a formulation in which the amount of water is reduced, for example, to less than 20% by weight, preferably less than 10% by weight, more preferably less than 5% by weight, more preferably less than 2% by weight, for example less than 1% by weight. The moisture content can be measured by any known method of the prior art. It can be measured, for example, according to the standard NF P94 050 of September 1995, "Determination of moisture content by weight of material: steam method."

[0043] The term "clay matrix" means one or more rocky materials based on layered silicates and / or aluminosilicates, and the clay matrix generally consists of fine particles derived from the alteration of three-dimensional skeletal silicates such as feldspar. Therefore, the clay matrix may include mixtures of rocky materials such as kaolinite, illite, smectite, bentonite, chlorite, vermiculite, metakaolin, or mixtures thereof. The expression "raw clay matrix" within the scope of the present invention corresponds to a clay matrix that has not undergone a firing process. In particular, it means that it has not undergone any prior heat treatment. For example, this corresponds to a clay matrix that has not undergone a temperature rise above 300°C, preferably above 200°C, and more preferably above 150°C. In fact, the raw clay matrix can generally undergo a drying process that requires a temperature rise of substantially below 150°C, but no firing process is performed. The raw clay matrix preferably includes a mixture of rocky materials such as kaolinite, illite, smectite, bentonite, chlorite, vermiculite, or mixtures thereof.

[0044] Within the scope of the present invention, "anti-coagulation agent" or "de-coagulation agent" may correspond to a compound that dissociates aggregates and colloids in an aqueous suspension. Anti-coagulation agents have been used, for example, in drilling and oil extraction to make clay more fluid and facilitate extraction and drilling.

[0045] Within the scope of the present invention, "activating composition" may correspond to a composition that promotes the formation of a dense structure and thereby increases the mechanical strength of a material incorporating such an activating composition. In particular, "alkaline activating composition" contains at least one base, such as a weak base or a strong base.

[0046] The expression "metal oxide composition" may, within the scope of the present invention, refer to a composition containing a metal oxide such as an aluminate. In particular, a metal oxide composition contains more than 25% by weight of a metal oxide, preferably more than 30% by weight of a metal oxide, more preferably more than 40% by weight of a metal oxide, and even more preferably more than 45% by weight of a metal oxide. For example, a metal oxide composition contains more than 2% by weight of an aluminate, preferably more than 5% by weight of aluminate, more preferably more than 7% by weight of aluminate, and even more preferably more than 10% by weight of aluminate. Furthermore, the metal oxide corresponds to or may contain alkaline earth metal oxides. For example, a metal oxide composition may contain more than 10% by weight of calcium oxide, preferably more than 20% by weight of calcium oxide, more preferably more than 25% by weight of calcium oxide, and even more preferably more than 30% by dry weight of calcium oxide.

[0047] The metal oxide composition may contain chemical species other than metal oxides. For example, the metal oxide composition may contain, for example, more than 10% by weight of metalloid oxides, preferably more than 20% by weight of metalloid oxides, more preferably more than 25% by weight of metalloid oxides, and even more preferably more than 30% by weight of metalloid oxides. These mass concentrations can be easily measured by those skilled in the art using conventional techniques for analyzing metal oxides or metalloid oxides.

[0048] In particular, the expression "metal oxide composition" refers to a composition containing more than 50%, preferably more than 70%, more preferably more than 80%, and even more preferably more than 90% of metal oxides and / or metalloids (including aluminates). Preferably, the metal oxide composition corresponds to slag from metallurgy such as blast furnace slag or fly ash.

[0049] As detailed below, the "metal oxide composition" refers to a calcined metal oxide composition, that is, it has undergone a high-temperature step. This high-temperature step may be natural or artificial, and in this case, it is a high-temperature treatment. The high-temperature step is, for example, 500°C or higher, preferably 750°C or higher, and more preferably 900°C or higher. Even more preferably, it corresponds to treatment at a temperature of 1000°C or higher.

[0050] In the context of this invention, the terms "binder" or "building binder" can be understood as a formulation that ensures the hardening of building materials and subsequent aggregation of materials during hardening. Therefore, it is possible to ensure aggregation of sand and other granules with the components of the binder. The binder according to this invention is a hydraulic binder, i.e., hardening occurs in contact with water.

[0051] The term "Portland cement" refers to a hydraulic binder primarily composed of hydraulic calcium silicate, which sets and hardens through a chemical reaction with water. Portland cement typically contains at least 95% clinker and up to 5% secondary components such as alkali (Na₂O, K₂O), magnesia (MgO), gypsum (CaSO₄·2H₂O), or various trace metals.

[0052] In the sense of this invention, "building material" generally refers to elements including binder components, as well as granules and other additives. In particular, building materials within the scope of this invention meet the criteria of standard NF EN206-1. They can take various forms, such as mortar, concrete, or prefabricated elements such as concrete blocks. A "rapidly curing building material" is, in particular, one in which the minimum resistance to cylinder compression measured according to standard NF EN206-1 24 hours after the addition of water is 2 MPa or more, preferably 3 MPa or more, and more preferably 5 MPa or more.

[0053] The term "air-entraining agent" refers to an auxiliary agent intended to be incorporated into the building binder according to the present invention, whose main function is to generate uniformly sized pores within the building binder once the hardening is complete. Such an auxiliary agent may be, for example, a surfactant such as alkyl ether sulfate.

[0054] The term "moisture buffer value" or "MBV" represents a material's ability to exchange humidity with the environment. This allows for the estimation of the material's dynamic humid-heat behavior and is used in the construction field to determine thermal comfort, particularly the regulation of internal humidity in rooms and buildings. MBV is expressed in g / m². 2 Expressed in %RH, it indicates the average amount of water exchanged by adsorption or desorption when the surface of a material is exposed to changes in relative humidity (RH) over a certain period of time.

[0055] The moisture buffer value can be measured by any method known to those skilled in the art. For example, those skilled in the art can refer to the method described in "Durability and Hygroscopic Behavior of Biopolymer-Stabilized Soil Building Materials" Construction and Building Materials 259 (2020). In particular, the sample is placed in a climate chamber at 23°C and 33% relative humidity and left until its mass stabilizes (e.g., model climate chamber MHE612). Under these conditions, the sample is equilibrated after 15 days of storage. The sample is then subjected to a high-humidity cycle (8 hours at 75% RH) followed by a low-relative-humidity cycle (16 hours at 33% RH). The sample is weighed at regular intervals using an accurate laboratory scale to the nearest 0.01 g. After the two stabilizing cycles, the sample is removed from the climate chamber.

[0056]

number

[0057] In the context of this invention, the term "substantially equal" corresponds to a value that varies by less than 20%, preferably less than 10%, and more preferably less than 5% from the value being compared.

[0058] In the context of this invention, the term "prefabricated element" or "prefabricated component" can refer to building elements that have undergone a hardening step, such as concrete block-type elements that can be combined in a modular manner to construct a building. These prefabricated elements may or may not include reinforcing materials (e.g., beams, panels, stairs) (e.g., blocks, joists, tiles, plates).

[0059] In the context of this invention, the term "specific surface area" may correspond to clay adsorption capacity. This can be measured by the French standard NF P94-068, which provides a methodology for determining the methylene blue value of soil or rock material by methylene blue testing. Specific surface area can also be measured according to standard NF EN933-9+A1. In fact, there is a correlation between the adsorption of methylene blue molecules (g / 100g) due to electrostatic interaction and the measured specific surface area of ​​clay materials, which was demonstrated as early as 1950 by Dyal and Hendricks. Furthermore, specific surface area can also be measured by the BET (Brunauer, Emmett, Teller) method. This method is preferably implemented according to the recommendations of standard ISO 9277:2010. Simply put, specific surface area is estimated from the amount of adsorbed nitrogen in relation to the boiling point of liquid nitrogen and the pressure at normal atmospheric pressure. The information is interpreted according to the Brunauer, Emmett, Teller model (BET method).

[0060] In the sense of this invention, the expression "excavated clay" refers to clay obtained after the step of excavating soil, for example, during leveling and / or earthwork for construction, building, or embankment. For example, excavated clay may refer to quarry pulp, dredged sediment, or excavated / washed mud. In particular, these fine particles, mud, or sediment may be 100m 2 Exceeding / g, preferably 200m 2When the clay has a specific surface area greater than / g, or even more specifically includes smectite clay, it is preferable that the clay matrix content exceeds 20% by weight, and therefore they are particularly suitable for the present invention. In particular, within the scope of the meaning of the present invention, the excavated clay may or may not be moved outside the production site. Preferably, according to the advantages of the present invention, the excavated soil is used at the production site or at a distance of less than 200 km, preferably less than 50 km. Furthermore, advantageously, the excavated clay in relation to the present invention is untreated excavated clay, i.e., has not undergone a calcination process. In particular, this means that it has not undergone any prior heat treatment. For example, this corresponds to clayey soil that has not undergone a temperature rise of more than 300°C, preferably more than 200°C, more preferably more than 150°C. In fact, raw clay soil can generally undergo a heating step that requires a temperature rise substantially equal to 150°C, but a calcination step is not necessary. The calcination step may correspond to, for example, a heat treatment at a temperature of more than 600°C for at least 1 hour. Conventionally used clays have a relatively constant particle size profile with a size of less than 2 μm. Excavated clay soil may have different particle size profiles. In the context of the present invention, excavated clay soil may contain particles larger than 2 μm, preferably larger than 20 μm, preferably larger than 50 μm, for example larger than 75 μm, as measured according to standard ASTMD422-63. Preferably, excavated clay soil does not contain granules larger than 2 cm, as determined according to standard NF EN933-1.

[0061] The construction sector needs to evolve to improve productivity while addressing new social challenges. In this regard, manufacturers are proposing cement mixtures, such as more environmentally friendly cement mixtures containing, for example, 50% Portland cement, 30% slag, and 20% fly ash. High-performance concretes that may contain high-flow agents, such as self-compressing concrete or aerated concrete containing gypsum, lime, cement, and sand, are also being proposed.

[0062] Nevertheless, these solutions fail to combine productivity (i.e., curing speed and mechanical resistance) and significantly reduce carbon balance and comfort for the user (especially control of temperature and humidity levels).

[0063] To overcome this, the inventors have developed a new solution comprising a novel building binder formulation. This novel solution has the advantage of having significantly lower carbon dioxide emissions than most building binders and hydraulic binders (such as Portland cement) currently widely used in the world. Furthermore, these solutions can ensure optimal control of temperature and ambient humidity levels, and in some cases, can guarantee rapid hardening of building materials containing such binder formulations. In this regard, the binder according to the present invention consists of a raw clay matrix that has not undergone a firing process, which is an energy-intensive process that also produces greenhouse gas emissions, more specifically carbon dioxide. The present invention relates in particular to a building binder comprising a raw clay matrix, an anti-coagulant, and an activating composition, characterized in that the raw clay matrix comprises at least smectite, montmorillonite, or bentonite, preferably more than 10% by weight of smectite clay.

[0064] As shown in the examples, the method according to the present invention enables the production of building elements from a binder containing a high concentration of raw clay matrix (generally 10% or more, preferably 20% or more), which has a mechanical resistance of more than 10 MPa, preferably more than 12 MPa, in 28 days, and an MBV greater than 0.7, preferably greater than 1, more preferably greater than 1.3, and even more preferably greater than 1.5. In particular, the inventors have developed a building binder composition that enables the formation of building materials having a minimum compressive strength on a cylinder of more than 12 MPa, preferably more than 15 MPa, in 28 days as measured by standard NF EN206-1, and a moisture buffer value of more than 0.7, preferably more than 1, more preferably more than 1.2, and even more preferably more than 1.5.

[0065] The general and preferred properties of each component of the building binder according to the present invention will be described in detail below. These embodiments are applicable to both the building binder according to the present invention and other aspects of the invention, such as the method, the building material itself (including prefabricated elements), or the use of the building binder and building material.

[0066] Raw material clay matrix The raw clay matrix may contain, for example, at least one mineral species selected from illite, kaolinite, smectite, bentonite, vermiculite, chlorite, muscovite, halloysite, sepiolite, and attapulgite.

[0067] In particular, the raw clay matrix contains smectite, preferably montmorillonite. Specifically, the clay matrix contains at least 10% by weight of smectite, preferably montmorillonite, and more preferably at least 20% by weight of smectite.

[0068] In fact, the inventors have shown that when the raw clay matrix contains at least one raw clay from the smectite family, and especially when the at least one raw clay from the smectite family exceeds 10% by weight of the building binder, preferably at least 20% by weight of the building binder, this building binder makes it possible to produce building materials that combine mechanical properties and moisture buffering capacity.

[0069] The smectite family includes montmorillonite and bentonite.

[0070] Preferably, the raw clay matrix comprises at least two types of clay selected from the following: illite; smectite, preferably montmorillonite; kaolinite; bentonite; vermiculite; chlorite; muscovite; halloysite; sepiolite or attapulgite. This includes clays called interlayer clays, which are complex combinations of multiple clays. More preferably, the raw clay matrix comprises at least one mineral species selected from kaolinite, illite, smectite, bentonite, chlorite and vermiculite.

[0071] Table 1 below shows the chemical properties of these mineral species.

[0072] [Table 1]

[0073] As described above, according to a preferred embodiment, the building binder according to the present invention comprises at least two different types of clay, and includes smectite.

[0074] The type of clay can be determined by methods known to those skilled in the art. In particular, X-ray diffraction measurements can be used. For example, the following conditions can be used: • Equipment: Diffractometer, e.g., BRUKER D8 ADVANCE (Bragg-Brentano Geometry); for example, the following settings are available: copper tube (λKα1 ≈ 1.54 Å), generator power: 40 kV, 40 mA; primary optics: fixed slit 0.16°; solar slit 2.5°; secondary optics: solar slit 2.5°; LynXeye XE-T detector • Acquisition parameters: Scan at 4-90°²θ. Scan speed: 0.03°²θ / sec, Count time: 480 seconds per step, Rotation sample.

[0075] For example, the building binder according to the present invention comprises at least 10% by weight of raw clay matrix, preferably at least 20% by weight of raw clay matrix, more preferably at least 30% by weight of raw clay matrix, and even more preferably at least 40% by weight of raw clay matrix, for example, at least 50% by weight of raw clay matrix, or at least 60% by weight of raw clay matrix.

[0076] Furthermore, preferably, the building binder according to the present invention comprises up to 80% by weight of raw clay matrix, more preferably up to 70% by weight of raw clay matrix.

[0077] Therefore, in particular, the building binder according to the present invention may contain 20 to 80% by weight of a raw clay matrix, preferably 30 to 80% by weight or 40 to 80% by weight of a raw clay matrix, more preferably 40 to 70% by weight of a raw clay matrix.

[0078] Preferably, the raw clay matrix of the building binder according to the present invention contains at least 20% by weight of smectite, for example, at least 30% by weight of smectite, preferably at least 40% by weight of smectite, more preferably at least 50% by weight of smectite, and even more preferably at least 60% by weight of smectite.

[0079] In particular, the clay matrix according to the present invention may contain 20 to 80% by weight of smectite, preferably 30 to 70% by weight of smectite, or 40 to 60% by weight of smectite, more preferably 40 to 60% by weight of smectite.

[0080] Preferably, the smectite may be montmorillonite.

[0081] More preferably, the raw clay matrix of the building binder according to the present invention comprises at least one raw clay from the smectite family and at least one other raw clay selected from kaolinite, illite, chlorite, and vermiculite. Even more preferably, the raw clay matrix of the building binder according to the present invention comprises smectite and at least one other raw clay selected from kaolinite, illite, bentonite, montmorillonite, chlorite, and vermiculite.

[0082] More preferably, the building binder comprises excavated soil containing a raw clay matrix. It may contain at least 2% by weight, preferably at least 4% by weight, and more preferably at least 6% by weight of silt particles. The silt particles are particularly particles having a diameter of 2 μm to 125 μm, preferably 2 μm to 50 μm.

[0083] The excavated clay may be advantageously pre-treated, the pre-treatment being selected from crushing, sorting, sieving and / or drying of the excavated clay. Pre-treatment may include, for example, fractionation.

[0084] The building binder according to the present invention has the advantage of being able to contain a large amount of raw clay matrix without changing the moisture absorption or mechanical properties of the building material, and in addition to moisture buffering capacity, it may be possible to manufacture building materials with improved curing time compared to commonly used building materials.

[0085] Anti-coagulation agent Many compounds can act as anti-aggregation agents, and many of them are generally known to those skilled in the art.

[0086] In relation to the present invention, the anti-coagulation agent is particularly a nonionic surfactant such as polyoxyethylene ether. The polyoxyethylene ether can be selected from, for example, poly(oxyethylene) lauryl ether.

[0087] The anti-coagulant may be an anionic agent such as an anionic surfactant. In particular, the anionic agent can be selected from alkylaryl sulfonates, amino alcohols, fatty acids, humicates (e.g., sodium humate), carboxylic acids, lignosulfonates (e.g., sodium lignosulfonate), polyacrylates, carboxymethylcellulose, and mixtures thereof.

[0088] The anti-coagulant may be a polyacrylate, which can be selected from, for example, sodium polyacrylate and ammonium polyacrylate.

[0089] The anti-flocculating agent may be an amine selected from, for example, the following: 2-amino-2-methyl-1-propanol; mono, di, or triethanolamine; isopropanolamine (1-amino-2-propanol, diisopropanolamine, triisopropanolamine) and N-alkylated ethanolamine.

[0090] Alternatively, the anti-coagulation agent may be a mixture of compounds, for example, a mixture comprising at least two compounds selected from nonionic surfactants, anionic agents, polyacrylates, amines, and organophosphorus compounds.

[0091] The anti-flocculating agent may be an organic anti-flocculating agent. According to the present invention, the organic anti-flocculating agent contains at least one carbon atom, preferably at least one carbon-oxygen bond. Preferably, the anti-flocculating agent is selected from: lignosulfonates (e.g., sodium lignosulfonate), polyacrylates, humicates, polycarboxylates such as ether polycarboxylates, and mixtures thereof. More preferably, the anti-flocculating agent contains humicates, lignosulfonates and / or polyacrylates.

[0092] The anti-coagulant is preferably in powder form (such as salt).

[0093] However, the present invention is not limited to the above-described anti-coagulant. Any type of anti-coagulant known to those skilled in the art can be used instead of the above-described anti-coagulant.

[0094] In particular, the anti-flocculation agent corresponds to at least 0.5% by weight of the raw clay matrix, preferably at least 1% by weight, more preferably at least 2% by weight, and even more preferably at least 3% by weight, for example, at least 4% by weight of the raw clay matrix. Furthermore, the anti-flocculation agent can correspond to up to 5% by weight of the raw clay matrix.

[0095] In particular, the anti-flocculation agent corresponds to at least 0.1% by weight of the building binder, preferably at least 0.5% by weight of the building binder. Furthermore, the anti-flocculation agent may correspond to up to 5% by weight of the building binder, preferably up to 4% by weight of the building binder, more preferably up to 3% by weight of the building binder, and even more preferably up to 2% by weight of the building binder.

[0096] In fact, using anti-flocculation agents at such concentrations, the building binder according to the present invention can be used in combination with the activating composition to form a material with advantageous humid and mechanical properties. Furthermore, to avoid deterioration of the mechanical properties of the building material, it is prudent not to exceed a certain percentage of the anti-flocculation agent. If the concentration of the anti-flocculation agent combined with the raw clay matrix and the activating composition is too high, the mechanical performance and / or MBV performance may decrease.

[0097] activation composition The activating composition is preferably an alkaline activating composition.

[0098] The alkaline activating composition contains at least one base, such as a weak base or a strong base. The activating composition may contain one or more compounds having a pKa of preferably 8 or higher, more preferably 10 or higher, more preferably 12 or higher, and even more preferably 14 or higher.

[0099] Therefore, alkaline activating compositions may include sulfates, hydroxides, carbonates, lactates, organic phosphates, or combinations thereof.

[0100] Preferably, the alkaline activating composition contains a hydroxide.

[0101] In particular, the alkaline activating composition may include a mixture of sodium sulfate / calcium sulfate and sodium chloride / calcium chloride.

[0102] Preferably, the alkaline activating composition contains a carbonate. In particular, the alkaline activating composition may contain a mixture of sodium silicate or potassium silicate and sodium carbonate or potassium carbonate. The activating composition may also contain an alkaline compound, preferably a strong base.

[0103] Advantageously, the activation composition contains an oxide of a metal having at least two valence electrons. In fact, such a composition improves the moisture buffering value compared to alkaline activation compositions based on sulfates, hydroxides, carbonates, lactates, organophosphates, or combinations thereof. In particular, the activation composition may contain at least 40% by weight of at least one metal oxide corresponding to an oxide of a metal having at least two valence electrons. For example, at least 40% by weight may correspond to several different metal oxides. However, the activation composition preferably contains a single oxide of a metal having at least two valence electrons, or more than 50% by weight of this metal oxide, if the latter is an alkaline activation composition. Preferably, the activation composition contains at least 50% by weight, more preferably at least 60% by weight, and even more preferably at least 80% by weight of at least one metal oxide corresponding to an oxide of a metal or alkaline earth having at least two valence electrons.

[0104] For example, the presence of metal oxides having at least two valence electrons can be identified by X-ray fluorescence spectroscopy (XRF) and / or X-ray diffraction (XRD).

[0105] The alkaline activating composition may contain an organophosphorus compound such as sodium tripolyphosphate. Preferably, the organophosphorus compound is in the form of at least 2% by weight of the building binder.

[0106] Preferably, the alkali-activating composition contains a lactate such as sodium lactate, potassium lactate, and / or lithium lactate.

[0107] As described below, the activating composition may be a liquid composition. In particular, the activating composition may be an aqueous composition. As will be described later, its use can be combined with the addition of water during the formation of the building binder according to the present invention. Alternatively, the activating composition may be in solid form, for example, in powder form. The indicated percentage of the alkaline activating composition corresponds to the dry weight of the composition.

[0108] The activating composition is present, for example, in an amount of at least 2% by the dry weight of the building binder.

[0109] Preferably, the building binder contains 2% to 50% by dry weight of an alkaline activating composition. More preferably, the building binder contains 2% to 40% by dry weight of an alkaline activating composition. Even more preferably, the building binder contains 10% to 20% by dry weight of an alkaline activating composition.

[0110] As shown in the examples, the required concentration of the alkaline activating composition can vary considerably depending on its composition. Therefore, the building binder according to the present invention may contain 20% to 40% by weight of the alkaline activating composition. This is especially true when the alkaline activating composition contains hydroxides. Alternatively, the building binder according to the present invention may contain 2% to 10% by weight of the alkaline activating composition. This is especially true when the alkaline activating composition contains carbonates. Finally, the building binder according to the present invention may contain 10% to 30% by weight of the alkaline activating composition, preferably 15% to 25% by weight of the activating composition.

[0111] The presence of components of the activating composition can be identified by spectroscopic measurements that depend on the activating composition used. For example, infrared spectroscopy can be used to identify the components of the composition in building materials.

[0112] Calcined metal oxide composition As shown in the examples, the building binder according to the present invention preferably contains less than 15% by weight, more preferably less than 10% by weight, less than 8% by weight, less than 5% by weight, less than 3% by weight, or less than 2% by weight of Portland cement, and even more preferably does not contain Portland cement.

[0113] In fact, the presence of Portland cement leads to a decrease in moisture buffering capacity.

[0114] The metal oxide composition advantageously includes metal oxides selected from iron oxides such as FeO, Fe3O4, Fe2O3, alumina Al2O3, manganese(II) oxide MnO, titanium(IV) oxide TiO2, magnesium oxide MgO, and mixtures thereof. It may also include metal oxides selected from calcium oxide and magnesium oxide.

[0115] Metal oxide compositions may also include aluminosilicates.

[0116] The composition of the metal oxide can be selected from, for example, the following: Blast furnace slag, • Volcanic ash, fly ash, silica fume, or pozzolanes such as metakaolin, • Ash from plants such as rice ash, • Bauxite residue, or • A combination of those.

[0117] Preferably, in the calcined metal oxide composition, the metal oxide is a transition metal oxide. The metal oxide is preferably derived from, for example, the composition of blast furnace slag formed when producing cast iron from iron ore.

[0118] The inventors confirmed the importance of the mass amount of metal oxide combined with the raw clay matrix. Preferably, the building binder contains at least 10% by weight of metal oxide.

[0119] For example, the building binder according to the present invention may contain at least 15% by weight of a blast furnace slag composition.

[0120] Advantageously, the building binder contains, for example, 10% by weight, preferably at least 10% by weight, and more preferably at least 20% by weight, of an aluminosilicate obtained from a calcination method.

[0121] For example, the building binder may contain at least 20% by weight of a calcined aluminosilicate composition, or the calcined metal oxide composition may contain aluminosilicate equivalent to at least 20% by weight of the building binder.

[0122] Aluminosilicates can be obtained, for example, from alumina, red clay, fly ash, blast furnace slag, or metakaolin.

[0123] While not limited to theory, the balance between the amount of calcined metal oxide composition and raw clay matrix, when combined with an alkaline activating composition, strengthens the bonds between clay sheets and imparts its mechanical properties to the binder, thanks to the anti-flocculation agent and the type of clay selected, while maintaining optimal moist heat properties. This is especially true when the clay matrix contains smectite, which the inventors have found to be particularly suitable for producing building materials with high MBV values ​​(e.g., >0.7, or preferably greater than 1) when combined with an anti-flocculation agent and an activating composition.

[0124] Furthermore, the inventors confirmed that a specific ratio between the mass of the metal oxide composition and the mass of the raw clay matrix allows for an appropriate balance between mechanical resistance, humidity measurement capability, and curing speed.

[0125] Advantageously, the composition of the metal oxide and the raw clay matrix are present in the building binder such that the mass ratio of the raw clay matrix to the composition of the metal oxide is 6 or less, preferably 4 or less, and more preferably 2 or less.

[0126] For example, the metal oxide composition and the raw clay matrix are present in the building binder such that the mass ratio of the raw clay matrix to the metal oxide composition is preferably 0.3 or more, more preferably 0.5 or more, and even more preferably 1 or more.

[0127] For example, the metal oxide composition and the raw clay matrix are present in the building binder such that the mass ratio of the raw clay matrix to the metal oxide composition is in the range of 0.3 to 3, more preferably between 1 and 3, and even more preferably between 1 and 2.

[0128] Advantageously, the metal oxide composition and the anti-flocculation agent are present in the building binder such that the mass ratio of the metal oxide composition to the anti-flocculation agent is 12 or more, preferably 15 or more.

[0129] In particular, metal oxide compositions, also known as calcined metal oxide compositions, constitute 20% to 70% by weight of the building binder.

[0130] Preferably, the metal oxide composition, also called a calcined metal oxide composition, is in the form of 35% to 65% by weight of the building binder.

[0131] More preferably, the metal oxide composition, also called a calcined metal oxide composition, is in the form of 40% to 65% by weight of the building binder.

[0132] The presence of components of a calcined metal oxide composition can be identified by spectroscopic analysis methods that depend on the calcined metal oxide composition used. For example, scanning electron microscopy, scanning electron microscopy combined with a microprobe, or X-ray fluorescence spectroscopy (XRF) and / or X-ray diffraction (XRD) measurements can be used to identify the components of a calcined metal oxide composition in building materials.

[0133] The building binder may contain many other compounds. For example, it may preferably contain an auxiliary agent equivalent to at least 1% by weight of the binder. In particular, the auxiliary agent is an air mixer. Those skilled in the art can use, for example, those known in conventional concrete.

[0134] As detailed above, according to the present inventors, combining blast furnace slag, fly ash, etc. with raw material clay and an activating composition (preferably alkaline) to produce a building material with good MBV (i.e., 0.7 or higher) that can harden quickly has not been proposed before. In particular, combining blast furnace slag, fly ash, etc. with a clay matrix containing at least one raw material clay from the smectite family (at least one raw material clay from the smectite family corresponds to at least 20% by weight of the building binder and activating composition), and an activating composition (preferably alkaline) has not been proposed before to produce a building material with good MBV that can harden quickly. These building binder compositions further contain less than 15% by weight of Portland cement.

[0135] Furthermore, among all the formulations, compositions, or binders according to the present invention that can be effectively used in the methods according to the present invention, the inventors have identified specific formulations of building binders that are novel in themselves and have a reduced carbon balance, rapid curing properties, moist heat properties, and high mechanical performance. These novel and particularly effective formulations constitute part of the subject matter of the present invention in themselves.

[0136] The present invention also relates to a building binder comprising a raw clay matrix, an anti-coagulant, and an activating composition, wherein the building binder includes: · At least 40% by weight of raw clay matrix (the raw clay matrix comprises at least one raw clay from the smectite family, the at least one raw clay from the smectite family equivalent to at least 20% by weight of the building binder); and • Portland cement containing less than 15% by weight.

[0137] The present invention also relates to a building binder comprising a raw clay matrix, an anti-coagulant, and an activating composition, wherein the building binder includes: • At least 40% by weight of raw clay matrix (the raw clay matrix comprises at least one raw clay from the smectite family, and the at least one raw clay from the smectite family corresponds to at least 20% by weight of the building binder); • At least 35% by weight of blast furnace slag; and • Portland cement containing less than 15% by weight.

[0138] The present invention also relates to a building binder comprising a raw clay matrix, an anti-coagulant, and an activating composition, wherein the building binder includes: • At least 40% by weight of raw clay matrix (the raw clay matrix comprises at least one raw clay from the smectite family, and the at least one raw clay from the smectite family corresponds to at least 20% by weight of the building binder); • Portland cement less than 15% by weight; and • At least 0.5% by weight of an anti-flocculation agent (the anti-flocculation agent includes an organic compound selected from humicates, lignosulfons, and polyacrylates).

[0139] The present invention also relates to a building binder comprising a raw clay matrix, an anti-coagulant, and an activating composition, wherein the building binder includes: • At least 40% by weight of raw clay matrix (the raw clay matrix comprises at least one raw clay from the smectite family, and the at least one raw clay from the smectite family corresponds to at least 20% by weight of the building binder); • Portland cement less than 15% by weight; and • At least 15% by weight of an activator (the activator contains at least 70% by weight of at least one metal oxide corresponding to a metal oxide having at least two valence electrons).

[0140] According to another aspect The present invention relates to a method for preparing a building binder, at least 100 m 2A combination of an anti-flocculation and activating composition for a raw clay matrix containing a mixture of at least two types of clay having a specific surface area equal to / g. use Regarding this matter. In particular, the raw clay matrix is ​​at least 100m 2 Specific surface area equal to / g, at least 150m² 2 Specific surface area equal to / g, at least 200m² 2 A specific surface area equal to / g, or at least 250m² 2 It contains at least one clay having a specific surface area equal to / g. Preferably, the raw clay matrix is ​​at least 100m 2 Specific surface area equal to / g, at least 150m² 2 Specific surface area equal to / g, at least 200m² 2 A specific surface area equal to / g, or at least 250m² 2 It contains at least two clays having a specific surface area equal to / g.

[0141] The present invention also relates to a combination of an anti-flocculation and activating composition for a raw clay matrix containing at least one raw clay from the smectite group (the at least one raw clay from the smectite group corresponds to at least 20% by weight of the building binder) for preparing a building binder. use Regarding this matter, the building binder contains less than 15% by weight of Portland cement.

[0142] The building binder according to the present invention can be used to manufacture cladding elements, particularly floor cladding such as tiles, slabs, cobblestones or curbs, interior or exterior facade elements, brick slips, panel elements, or wall cladding such as tile-type roofing materials, and can be used to manufacture extruded or molded building modules such as bricks, or to manufacture various extruded shapes.

[0143] The building binder according to the present invention can be used in the manufacture of composite materials such as prefabricated panel-type building panels, prefabricated blocks such as doors or window lintels, prefabricated wall elements, or any other prefabricated building elements.

[0144] The building binder according to the present invention can be used in the manufacture of thermal insulation modules (density less than 1.5 kg / L, preferably less than 1.2 kg / L, more preferably less than 1.0 kg / L, and more preferably less than 0.7 kg / L) such as partition panels and light-insulating building modules.

[0145] The present invention also relates to the use of the building binder according to the present invention for performing additive manufacturing. In particular, the implementation of additive manufacturing can be carried out using an automated 3D construction system such as a 3D printer. Such additive manufacturing makes it possible to manufacture building elements, buildings and houses, and even decorative items.

[0146] The building binder according to the present invention can be used in the form of a two-component system (one of which is a solid component and the other is a liquid component, or two of which are paste-like components) for the manufacture of mastic, adhesives, or sealing mortars.

[0147] According to another aspect The present invention relates to a binder for construction. Manufacturing method The present invention relates, in particular, to the manufacture of a building binder that enables the production of building materials having a high moisture buffering capacity (i.e., greater than 0.75).

[0148] As previously mentioned, the raw clay matrix may contain at least one mineral species selected from the following: illite; smectite, preferably montmorillonite; kaolinite; bentonite; vermiculite; chlorite; muscovite; halloysite; sepiolite or attapulgite. This includes clays called interlayer clays, which are complex combinations of multiple clays.

[0149] This method particularly involves a mixture of a raw clay matrix, an anti-coagulation agent, and an activating composition. The raw clay matrix comprises at least one raw clay from the smectite family, the at least one raw clay from the smectite family corresponding to at least 20% by weight of the building binder. Furthermore, the building binder preferably comprises less than 15% by weight of Portland cement.

[0150] This method may include a step of homogenizing or mixing to obtain a building binder. This homogenizing or mixing step can be continued for at least 45 seconds, preferably at least 60 seconds, more preferably at least 90 seconds, for example, less than 30 minutes, preferably less than 10 minutes. More preferably less than 5 minutes.

[0151] After the mixing step, the method according to the present invention may include the addition of additives or materials that allow for the modification of the mechanical properties of the final building material.

[0152] The added materials may be, for example, granules (whether recycled or not) selected from fillers, powders, sand, rubble, gravel, and / or fibers, and optionally pigments. Generally, the granules may correspond to sand, or sand and other aggregates such as rubble, gravel, pebbles, hemp sieves, and / or aggregates of other plants.

[0153] This method may also involve the addition of a plasticizer or a fluidizer.

[0154] This method may also involve the addition of fibers. The fibers are selected from, for example, plant fibers such as flax, cotton, hemp, cellulose, bamboo, and pampas grass fibers; synthetic fibers such as metal, glass, carbon, and polypropylene fibers; and mixtures thereof. The presence of fibers makes it possible to form building materials with improved mechanical and thermal insulation properties.

[0155] This method may also include the addition of aggregate. The aggregate may be selected from, for example, gravel, crushed material, recycled concrete, and mixtures thereof.

[0156] This method may also involve the addition of additives. These additives may be selected from, for example, synthetic or natural rheological regulators, shrinkage inhibitors, water-retaining agents, air-entraining agents, synthetic resins, and mixtures thereof.

[0157] The preparation of the building binder according to the present invention involves, in particular, the addition of sand and water. The sand can be generated from chips, especially in the case of "in-situ" concrete. The sand may be desert sand.

[0158] The building materials that can be obtained can be selected from, for example, mortar, coatings, and gypsum.

[0159] In certain embodiments, a construction binder is used to prepare prefabricated elements.

[0160] therefore, According to another aspect The present invention is Method for manufacturing prefabricated elements Regarding this, in addition to moisture buffering capacity, it is important that the building binder enables the rapid hardening of the building material. Prefabricated elements are prepared from a building binder, which in particular comprises a raw clay matrix, an anti-coagulant, and an activated composition to which granules and water are added.

[0161] In particular, in the building binder used in this method, the raw material clay matrix contains at least one raw material clay from the smectite family. The at least one raw material clay from the smectite family corresponds to at least 20% by weight of the building binder. The building binder contains less than 15% by weight of Portland cement. As described above, this method benefits from embodiments of the building binder. Therefore, more preferably, the building binder contains less than 10% by weight, less than 8% by weight, less than 5% by weight, or less than 3% by weight of Portland cement, and even more preferably, does not contain Portland cement.

[0162] Figure 1As shown, method 100 according to the present invention includes the steps of supplying a building binder 110, mixing the components of the building material binder with granules and water 120, and curing the mixture 130.

[0163] As shown in the illustration, the method according to the present invention may also include a step 101 of preparing a mold, a step 140 of removing the prefabricated elements from the mold, and a step 150 of drying the prefabricated elements.

[0164] However, as will be explained in the examples, the inventors have determined the selection of clay and usage conditions that enable the production of building materials that allow for high levels of mechanical resistance and rapid hardening, despite the high levels of raw clay. In particular, under the selected conditions, the clay matrix can be present in more than 10% by weight of the building material binder, preferably more than 20% by weight of the building material binder.

[0165] Therefore, it is possible to obtain materials with a moisture buffering capacity of 0.75 or higher and a low carbon balance, while respecting the productivity requirements of the construction industry.

[0166] In particular, as described in the examples, the raw clay matrix contains at least one raw clay from the smectite family. The best results in terms of moisture buffering capacity are obtained when the raw clay matrix contains one or more of these clays.

[0167] The inventors determined that, in addition to selecting the appropriate clay, it is necessary to add a decoagulant and perform heat treatment in order to obtain a building material that hardens quickly and has high moisture buffering capacity.

[0168] Therefore, advantageously, in the context of method 100 for manufacturing prefabricated elements according to the present invention, the hardening step 130 includes heat treatment of the mixture. In fact, the combination of performing heat treatment and the presence of smectite clay makes it possible to obtain a building material having a moisture buffering capacity of 0.75 or more while rapidly hardening.

[0169] As shown in Figure 1, the method 100 for manufacturing a prefabricated element according to the present invention includes a step 101 of preparing a mold, which involves, for example, the use of a release agent or mold oil, the use of shims for reinforcement, or the use of a system that allows for an airtight cover of the part or cured product.

[0170] Furthermore, the method according to the present invention may include a first step of preparing a building binder mixture. The step of preparing the building binder mixture may include, for example, dry mixing. In fact, most or all of the components of the building binder can be used in a dehydrated form.

[0171] Alternatively, some of the components can be mixed in a dry state, while other components can be added in liquid form.

[0172] In particular, the method according to the present invention includes step 120 of mixing the components of a building binder with granules and water.

[0173] Here, the water-to-dry substance mass ratio of the composition, referred to as the building binder, is preferably controlled. The water / dry substance ratio is preferably less than 1, more preferably 0.6 or less, and even more preferably 0.5 or less. This ratio does not take into account the amount of granules added.

[0174] Conventionally, granules can correspond to natural granules, artificial granules, or recycled granules. The granules may further contain mineral granules, i.e., mainly mineral materials and / or plant granules, i.e., mainly plant-derived materials. The granules may further contain marine granules, i.e., mainly organic or inorganic materials originating from the seabed, such as siliceous granules and limestone materials (e.g., marl sand and shell sand). Mineral granules can correspond to, for example, sand, rubble, gravel, fillers (or fine materials), powders, fossil waste, and combinations thereof.

[0175] Plant granules include, for example, wood (chips or fibers), hemp, straw, hemp sieve, Japanese pampas grass, sunflower, cattail, corn, flax, rice husks, wheat bales, rapeseed, seaweed, bamboo, cellulose stuffing, shredded cloth, and combinations thereof.

[0176] In particular, when the building material or prefabricated element according to the present invention contains plant granules, it preferably contains at least 10% by weight of plant granules, preferably at least 15% by weight of plant granules, more preferably at least 20% by weight of plant granules, and even more preferably at least 25% by weight of plant granules. Generally, when plant granules are used, the building material or prefabricated element according to the present invention preferably contains up to 60% by weight of plant granules, more preferably up to 50% by weight of plant granules. For example, the building material or prefabricated element according to the present invention may preferably contain 10% to 50% by weight of plant granules, more preferably 15% to 35% by weight of plant granules. When plant granules are used in the compressed concrete block according to the present invention, they may be combined with mineral granules such as sand. This can improve mechanical performance.

[0177] Such mixing processes can be advantageously carried out in mixers and truck mixers, or more generally, in any apparatus suitable for mixing building binders, but these are not the only options. For example, ultrasonic dispersion devices can be used. Furthermore, the mixing step 120 can be carried out for a duration of up to 24 hours, preferably up to 12 hours, and more preferably up to 6 hours. Advantageously, in the context of method 100 for manufacturing prefabricated elements, it could be as little as a few tens of minutes, and therefore less than an hour, or even a few tens of seconds. In fact, the mixture can be manufactured in a situation where the mixture is made in a press, whether or not it is vibrating, just seconds before it is filled into a mold.

[0178] Before any curing step 130, during or before the mixing step 120, the method 100 according to the present invention may include the addition of additives or materials that can alter the mechanical properties of the final building material.

[0179] Therefore, this method may also involve the addition of plasticizers or fluidizers.

[0180] Method 100 may also include the addition of fibers. The fibers are selected from, for example, plant fibers such as flax, cotton, hemp, cellulose, bamboo, and pampas grass fibers, synthetic fibers such as metal, glass, carbon, and polypropylene, and mixtures thereof. The presence of fibers advantageously enables the formation of building materials with improved mechanical and thermal insulation properties while maintaining moisture buffering capacity.

[0181] Method 100 may also include the addition of aggregate. The aggregate is selected from, for example, gravel, crushed material, recycled concrete, and mixtures thereof.

[0182] Method 100 also selects the additive from, for example, synthetic or natural rheological control agents, shrinkage inhibitors, water-retaining agents, air-entraining agents, synthetic resins, and mixtures thereof.

[0183] Method 100 according to the present invention may include a step 130 of curing the mixture.

[0184] The curing step 130 is generally known to those skilled in the art who can perform it. This can be done, for example, by keeping the product in a curing chamber, or by covering it, or by spraying water or a curing agent and covering it.

[0185] The curing step 130 may last for a maximum of 48 hours, preferably a maximum of 24 hours, more preferably less than 23 hours, and may be substantially equal to 20 hours. The curing step 130 generally lasts for at least 2 hours, preferably at least 6 hours, and more preferably at least 12 hours.

[0186] Preferably, in the context of the present invention, the curing step 130 is performed in an airtight mold. An airtight mold is advantageous in that it allows for limiting or eliminating exchange between the mixture and the outside air.

[0187] The hardening step may or may not include heat treatment. However, even when heat treatment is performed, it is carried out at temperatures below 500°C, so the hardened clay always remains in its raw material state, and bound water is not removed. In other words, since the clay is not fired, it can still be considered as raw material clay. The effectiveness of the pozzolanic reaction on the mechanical properties of concrete differs from that observed when using metakaolin, and is not related here to the complete dehydroxylation and amorphization of the clay (Konan and al., Etude comparative de la deshydroxylation / amorphisation dans deux kaolins de cristallinite differente. J. Soc. Ouest-Afr. Chim. (2010) 030; 29 - 39). Furthermore, the reaction with the activating composition does not change the structure of the raw material clay, and this can always be confirmed in the final material by scanning electron microscopy, etc.

[0188] In the context of the present invention, the heat treatment is preferably carried out at a temperature above 25°C, preferably above 30°C. However, in order to respect a preferred energy balance, the curing step is carried out at a temperature below 120°C, preferably below 100°C, and more preferably below 80°C. For example, the thermosetting step is carried out at a temperature of 20°C to 90°C, preferably between 25°C and 80°C, and even more preferably between 25°C and 65°C.

[0189] Furthermore, the heat treatment can be performed throughout the entire curing step, or it can be performed over a shorter period of time. Therefore, it is preferable that the heat treatment be performed over a period of 20 hours or less, more preferably less than 15 hours, and even more preferably less than 10 hours.

[0190] As shown in Figure 1, the method according to the present invention may include a step 140 of removing the prefabricated element from the mold. The step 140 of removing from the mold is generally known to those skilled in the art who know how to carry it out. This step is facilitated by a step of preparing the mold, which may involve, for example, the use of a release agent or mold oil, the use of shims for reinforcement, or the use of a system that allows for an airtight cover of the part.

[0191] Finally, the method according to the present invention may include a step 150 of drying the prefabricated elements. The drying step 150 is generally known to those skilled in the art who know how to carry it out. This step may be carried out under special conditions, in particular in an environment protected from wind, frost, sun, etc.

[0192] In the context of various embodiments and features of the present invention, the inventors have for the first time obtained a prefabricated element or building material having a moisture buffer value of 0.75 or higher, preferably 0.1 or higher, and more preferably 1.2 or higher.

[0193] Furthermore, certain prefabricated elements or building materials harden quickly, and the minimum compression resistance on a cylinder within 20 hours of the hardening step, as measured according to standard NF EN206-1, is 16 MPa or higher, preferably 18 MPa or higher, and more preferably 20 MPa or higher. Therefore, the building binder is a particularly fast-curing building binder, and similarly, the building material according to the present invention is a fast-curing building material.

[0194] The method according to the present invention may incorporate the above-described embodiments of the building binder (in particular, features relating to the main components of the building binder: raw clay matrix, anticoagulant, activating composition, and calcined metal oxide composition), whether they are advantageous, specific, or preferred.

[0195] According to another embodiment The present invention includes a building binder according to the present invention. building materials This relates to the present invention, in particular to a construction binder formed according to the present invention. building materialsRegarding this, building materials can be selected from, for example, mortar, coatings, gypsum, insulation, lightweight concrete, and prefabricated elements.

[0196] This invention relates to building materials obtained or likely to be obtained by the method according to the present invention.

[0197] Advantageously, the building binder according to the present invention is used to form building materials such that the filler accounts for 200% to 900% by weight of the building binder. For example, in the building material according to the present invention, the building binder according to the present invention preferably accounts for 10% to 33% by weight of the building material.

[0198] In particular, the building material formed from the building binder according to the present invention contains at least 5% by weight of raw clay from the smectite group. Preferably, the building material contains at least 8% by weight of raw clay from the smectite group, and more preferably at least 10% by weight of raw clay from the smectite group.

[0199] Advantageously, the building material formed from the building binder according to the present invention also contains at least 5% by weight of at least one metal oxide corresponding to an oxide of a metal having at least two valence electrons. Preferably, at least 5% by weight may be formed from several different metal oxides. These metal oxides may originate from several sources. Preferably, the metal oxide formed from a metal having at least two valence electrons will be included in the activated composition and / or the calcined metal oxide composition. Preferably, the building material contains at least 10% by weight, more preferably at least 15% by weight, and even more preferably at least 20% by weight of at least one metal oxide corresponding to an oxide of a metal having at least two valence electrons.

[0200] The building material according to the present invention may also contain plant fibers, preferably hemp sieves.

[0201] The building material according to the present invention may contain diatom shells.

[0202] The building material according to the present invention may have a moisture buffer value of 0.75 or higher, preferably 1 or higher, and more preferably 1.2 or higher.

[0203] The building material according to the present invention may have a minimum resistance of 2 MPa or more, preferably 3 MPa or more, and more preferably 5 MPa or more, to compression on a cylinder as measured by standard NF EN206-1.

[0204] The building material according to the present invention may have a minimum resistance of 8 MPa or more, preferably 10 MPa or more, to compression on a cylinder after 7 days, as measured according to the standard NF EN206-1.

[0205] Furthermore, the building materials according to the present invention may have a minimum resistance to compression on a cylinder after 28 days, measured according to the standard NF EN206-1, of 40 MPa or less, for example, 30 MPa or less, preferably 20 MPa or less as shown in the examples. However, in certain applications, the minimum compressive strength of the cylinder after 28 days may be significantly lower.

[0206] Preferably, the building material according to the present invention may have a minimum compressive strength in the range of 10 to 30 MPa, preferably 10 to 20 MPa, against compression on a cylinder after 28 days as measured according to the standard NF EN206-1.

[0207] The building material according to the present invention can be formed from a building binder that includes excavated soil containing a raw clay matrix.

[0208] The building binder according to the present invention can be used in the manufacture of the following: • Insulating building materials: Binder and lightweight granules of the "plant-based or porous" type according to the present invention. • Mortar and concrete sprayed in a dry or wet process, • Injected concrete / mortar, • Compressed concrete / mortar, • Extruded concrete / mortar, • Concrete form, Lightweight concrete: The building binder according to the present invention may include, for example, straw, rice husks, hemp sieves, seaweed, wood chips, sunflower, Sargassum, reeds, wheat husks, or other grains, and mixtures thereof. Fiber-reinforced concrete containing carbon, glass, polypropylene, flax, hemp, yucca, jute, kenaf, Mauritanian ampelodesmos, coconut, oil palm, date oil, banana, and pineapple fibers… • High-temperature performance concrete, • Liquid screed, mortar, • Building systems or prefabricated elements: Manufacturing of concrete blocks or concrete slabs (such as pillars) (especially silica fume, earth concrete, wooden frame / earth concrete joints, earth mortar walls, reinforced earth concrete) in a factory from the binder according to the present invention, and • Insulation module.

[0209] The present invention also relates to the use of the building binder according to the present invention for the manufacture of composite materials or prefabricated blocks.

[0210] Composite materials are, for example, prefabricated panel-type building panels, while prefabricated blocks are, for example, doors or window lintels, prefabricated wall elements, or any other prefabricated building elements.

[0211] Therefore, in particular, the present invention can be formed from a building binder according to the present invention. Prefabricated elements Regarding this, advantageously, this prefabricated element is formed from a building binder according to the present invention.

[0212] Preferably, this prefabricated element, such as a partition wall, is at least 1 m 2 , more preferably at least 1.5m 2 More preferably, at least 2m 2 It has a surface having a surface area.

[0213] Furthermore, the prefabricated elements may have a thickness between 0.3 cm and 20 cm, preferably between 0.5 cm and 10 cm, and more preferably between 1 cm and 7 cm.

[0214] Such prefabricated elements advantageously have a moisture buffer value of 0.75 or more, preferably 1 or more, more preferably 1.2 or more, and even more preferably 1.5 or more. This is because the prefabricated elements have a moisture buffer value of at least 1 m 2 , more preferably at least 1.5m 2 More preferably, at least 2m 2 This is particularly useful when the surface has a certain surface area.

[0215] Furthermore, the present invention is particularly suitable for prefabricated elements when they include excavated clay soil.

[0216] In particular, the building binder according to the present invention is especially suitable for manufacturing partitions. In fact, in order to form building walls and prefabricated partitions, durable building materials and a fast curing time are required, i.e., a compressive resistance of at least 2 MPa after 24 hours and 10 MPa or more after 28 days. Furthermore, when dry, it is necessary to have an MBV of greater than 0.8, preferably greater than 1.2, for example, 0.8 to 3.

[0217] Accordingly, the present invention relates to the use of a building binder according to the present invention for the manufacture of partitions, preferably prefabricated partitions, and more preferably partitions having a compressive strength of at least 2 MPa after 24 hours and more than 10 MPa after 28 days, and a dry MBV of 0.8 to 3.

[0218] Such use may include adding fillers such as sand or plant fibers such as hemp sieves to the building binder according to the present invention.

[0219] Advantageously, the building binder according to the present invention is used such that the filler accounts for 200% to 900% by weight of the building binder. For example, in a partition according to the present invention, the building binder according to the present invention preferably accounts for 10% to 33% by weight of the building material.

[0220] The present invention also relates to partitions manufactured from the building binder according to the present invention. Such partitions may contain other bio-derived materials. In particular, when the building binder according to the present invention is used in the manufacture of thermal insulation building materials, it may contain lightweight granules of plant origin.

[0221] Preferred embodiments of the present invention have been described in detail above.

[0222] Nevertheless, features of this embodiment, such as advantageous, specific, preferred, or undesirable features, can be combined with other embodiments described below.

[0223] In fact, the present invention also relates to a building binder comprising a raw clay matrix, an anti-flocculation agent and an activating composition, characterized in that the minimum resistance to compression on a cylinder, as measured according to standard NF EN206-1, is 12 MPa or more, preferably 15 MPa or more, over 28 days, and the moisture buffer value is 0.7 or more, preferably 1 or more, more preferably 1.2 or more, and even more preferably 1.5 or more. Advantageously, the building binder also includes a calcined metal oxide composition. In particular, the present invention relates to a building binder comprising a raw clay matrix, an anti-flocculation agent and an activating composition, which enables the preparation of building materials having a minimum resistance to compression on a cylinder, as measured according to standard NF EN206-1, of 12 MPa or more, preferably 15 MPa or more, over 28 days, and a moisture buffer value of 0.7 or more, preferably 1 or more, more preferably 1.2 or more, and even more preferably 1.5 or more, measured within 10 days, preferably 28 days, after production. Advantageously, the building binder further includes a calcined metal oxide composition. Advantageously, the building binder further comprises a calcined metal oxide composition.

[0224] The present invention also relates to a building binder comprising a raw clay matrix, a decoagulant, and an activating composition, wherein the raw clay matrix comprises a mixture of at least two types of clay, preferably the clay matrix comprises at least smectite. More preferably, the two types of clay comprise at least 30 m 2 Equivalent to / g, preferably at least 50m 2 Equivalent to / g, more preferably 100m 2 It has a specific surface area exceeding / g.

[0225] More preferably, the present invention relates to a building binder comprising a raw clay matrix, an anti-flocculation agent, and an activating composition, wherein the raw clay matrix comprises a mixture of at least two types of clay, for example, smectite, and the binder further comprises a calcined metal oxide composition. Advantageously, the calcined metal oxide composition is blast furnace slag. Preferably, the building binder comprises at least 20% by weight of the calcined metal oxide composition, more preferably at least 20% by weight of the blast furnace slag.

[0226] The present invention also relates to a building binder comprising a raw clay matrix, an anti-flocculation agent, an activating composition, and a calcined metal oxide composition, characterized in that the anti-flocculation agent comprises a lignosulfonate, a polyacrylate, a humicate, or a mixture thereof.

[0227] The present invention also relates to a building binder comprising a raw clay matrix, an anti-coagulation agent, an activating composition, and a calcined metal oxide composition, characterized in that it contains 30% to 70% by weight, preferably 40% to 60% by weight, of the raw clay matrix, and has the following characteristics: The ratio of (raw clay matrix) to (calcined metal oxide composition) is less than 6, preferably less than 4, and preferably 1 to 3. • The ratio of (calcined metal oxide composition) to (anti-flocculation agent) is greater than 12; Preferably, the calcined metal oxide composition is a slag obtained from metallurgy, such as blast furnace slag.

[0228] The present invention also relates to a building binder comprising a raw clay matrix, an anti-coagulant, an activating composition, and a calcined metal oxide composition, and is characterized by having the following: • 30% to 70% by weight, preferably 40% to 60% by weight, of raw clay matrix; • A calcined metal oxide composition in an amount of 15% to 45% by weight, preferably 20% to 40% by weight; Preferably, the raw material clay matrix contains at least two types of clay.

[0229] As illustrated by the following embodiments, the present invention provides a solution based on a mixture of a raw clay matrix, an anti-coagulant, and an activating composition to provide a building binder having similar mechanical properties to the standard while reducing carbon dioxide emissions. [Examples]

[0230] Manufacturing of building binders: In all the examples shown below, the formulations according to the present invention are prepared according to the same protocol, namely, a dry premix is ​​performed between the raw clay matrix, an anti-coagulant, and a predetermined amount of the activating composition. Water is then added and the solution is mixed at a low speed, i.e., substantially 60 revolutions per minute, for 30 seconds. Sand is then added to the premix and everything is mixed at a high speed, i.e., about 120 revolutions per minute, for 1 minute.

[0231] The water-to-dry substance ratio of the composition (also called a building binder) is adjusted to a value of 0.4 to 0.6.

[0232] In a specific example, the building material mortar contains 25% by weight of binder and 75% by weight of sand. Water is added to this mixture so that the mass ratio of water to the dry weight of the binder is adjusted to a value of 0.5.

[0233] The mortar, based on the building binder thus formed, is poured into a mold and left to mature at room temperature, or approximately 20 degrees Celsius, for 28 days.

[0234] Alternatively, the mortar can be poured into a mold and allowed to mature for less than 24 hours at room temperature, i.e., about 25°C, or preferably under heat treatment, during the curing process. During this curing step, the mold can be made airtight or the upper layer of the building material can be covered with the cured product to limit / prevent evaporation.

[0235] Method for measuring the mechanical properties of building binders: Once maturation is complete, the mechanical resistance is measured. The term mechanical strength of a construction binder means the resistance to compression, such compression being measured on prisms of 40 mm in width and 160 mm in length according to standard NF EN196-1, and expressed in megapascals (MPa).

[0236] How to measure MBV value: The moisture buffering value can be measured by any method known to those skilled in the art. For example, reference may be made to the method described in "Durability and hygroscopic behaviour of biopolymer-stabilized earth building materials", Construction and Building Materials 259 (2020). The sample is placed in a constant temperature chamber at 23°C and 33% relative humidity, and left until its mass becomes constant (for example, model constant temperature chamber MHE612). Under these conditions, the sample is equilibrated after 15 days of storage. Next, the sample is subjected to a high humidity cycle (8 hours at 75% RH), followed by a low relative humidity cycle (16 hours at 33% RH). The sample is weighed at regular intervals using a precision laboratory scale accurate to 0.01 g. After two stable cycles, the sample is removed from the climatic chamber.

[0237] [Formula] wherein Δm is the change in mass of the sample due to the change in relative humidity, S is the total exposed surface area, and Δ%RH is the difference between the humidity levels.

[0238] Comparison of the building binder according to the present invention with known building binders: Table 2 below shows different types of construction binders, known formulations and formulations according to the present invention. The mass of the components associated with each formulation is expressed as a percentage relative to the total mass (dry weight) of the construction binder.

[0239] [Table 2]

[0240] Accordingly, Table 2 shows the mechanical strength of a known construction binder (Binder CEM1), such as the CEM1 type construction binder well known under the name of "Portland" cement, which does not form part of the present invention, and its compressive strength is on the order of 45 MPa. It also shows the calculated moisture buffer value (MBV=0.41) for these prior art construction materials.

[0241] Table 2 also shows Formulation MUP1 according to the present invention. It is important to note that this formulation contains 1% anti-caking agent, but contains a small amount of raw clay matrix (20%), has the same mechanical resistance similar to that of Portland cement, but has far superior humidity properties (MBV=0.88).

[0242] Furthermore, MUP1 containing 20 wt% smectite has an MBV greater than 0.75 (0.88), while MUP0 containing 10 wt% smectite and 10 wt% kaolinite has an MBV below the limit of 0.75.

[0243] Similarly, MUP-Y0 containing about 40% kaolinite cannot reach an MBV value of 0.75 or higher, while MUP-Y1 containing about 40% smectite can reach an MBV value of 1.4.

[0244] Therefore, clays of the smectite family are very advantageous for the production of construction materials having moisture buffer capacity that can improve the comfort of occupants through temperature and humidity regulation.

[0245] Table 2 also shows that a mixture of clays (MUP-Y2), such as a 50 / 50 mixture of smectite and kaolinite, can significantly improve the moisture buffer capacity (MBV=1.3) while maintaining high compressive strength.

[0246] Regarding the inefficiency of adding raw clay to CEM1: Table 3 below shows the known cement formulation CEM1-X1 with added anticoagulants, and five cement formulations with different proportions of clays CEM1-X2, CEM1-X3, CEM1-X4, and CEM1-X5 added.

[0247] [Table 3]

[0248] CEM1-X1 achieves very high mechanical strength, but its MBV is insufficient (<0.75).

[0249] Surprisingly, adding 20% ​​raw clay, even in the presence of an anti-coagulant, leads to a decrease in the moisture properties and mechanical resistance of the building material.

[0250] When 40% raw clay (CEM1-X3) is combined with cement CEM1 and an anti-coagulant, the MBV increases compared to CEM1-X1, but is still insufficient (<0.75). Furthermore, the mechanical properties of the building material CEM1-X5 are strongly affected, reaching an insufficient level (<10).

[0251] Therefore, it is not possible to produce a binder with satisfactory MBV properties and mechanical strength properties using a combination of raw clay, CEM1, and an anti-flocculation agent.

[0252] The importance of blast furnace slag: Table 4 below shows the reference formulation MUPZ0, the formulation MUPZ1 according to the present invention, and the formulation MUPZ2 according to the present invention.

[0253] [Table 4]

[0254] Table 2 shows that compositions MUPZ1 and MUPZ2 can achieve MBV much higher than 0.75 by replacing Portland cement with an activated composition and a calcined metal oxide composition (e.g., blast furnace slag type or ash).

[0255] Furthermore, composition MUPZ2, which contains an organic anti-coagulant, has a compressive strength exceeding 25 MPa while having an MBV approximately equal to 2.

Claims

1. A building binder comprising a raw clay matrix, an anti-coagulant, a calcined metal oxide composition, and an alkaline activating composition, - Containing 10% to 30% of the alkaline activating composition by dry weight, - The building binder contains at least 40% by weight of the raw clay matrix, the raw clay matrix contains at least one raw clay from the smectite family, and the at least one raw clay from the smectite family corresponds to at least 20% by weight of the building binder. The building binder contains less than 15% by weight of Portland cement and at least 20% by weight of the calcined metal oxide composition. The anti-coagulation agent is an organic compound selected from lignosulfonates, polyacrylates, humicates, or mixtures thereof. The alkaline activating composition comprises sulfates, hydroxides, carbonates, lactates, organophosphates, or combinations thereof. - The calcined metal oxide composition is selected from blast furnace slag and pozzolanes selected from volcanic ash, fly ash, silica fume and metakaolin. A binder for construction, characterized by the following features.

2. The building binder according to claim 1, characterized in that the raw material clay matrix contains a mixture of at least two types of clay.

3. The raw clay matrix is ​​measured according to standard NFP94-068 and is at least 100 m 2 A building binder according to claim 1 or 2, characterized by comprising at least one clay having a specific surface area equal to / g.

4. The building binder according to claim 1, characterized in that the mass ratio of the raw clay matrix to the fired metal oxide composition is 1:1 or greater.

5. The building binder according to any one of claims 1 to 4, characterized in that the alkaline activating composition contains at least 40% by weight of at least one metal oxide corresponding to a metal oxide having at least two valence electrons.

6. A building binder according to any one of claims 1 to 5, characterized in that it includes excavated soil containing the aforementioned raw material clay matrix.

7. A building material that can be formed from a building binder according to any one of claims 1 to 6, - At least 2% by weight of at least one raw material clay from the smectite family, - Portland cement containing less than 3.75% by weight, and - At least 2% by weight of a calcined metal oxide composition Includes, Building materials whose moisture buffer value, measured 10 days or more after manufacturing, is 0.75 or higher.

8. The building material according to claim 7, characterized in that it contains at least two types of raw clay.

9. The building material according to claim 7 or 8, characterized by containing at least 5% by weight of at least one metal oxide corresponding to a metal oxide having at least two valence electrons.

10. The building material according to any one of claims 7 to 9, characterized in that, when measured according to standard NF EN206-1, the minimum resistance to compression of the cylinder after one day is 2 MPa or more.

11. A prefabricated element that can be formed from a building binder according to any one of claims 1 to 6, wherein the prefabricated element is: - Surface area of ​​at least 1 m 2 It has a surface with a thickness of 0.3 cm to 20 cm. - Contains at least 5% by weight of at least one raw material clay from the smectite tribe, - Contains at least 2% by weight of a calcined metal oxide composition, - Contains less than 3.75% by weight of Portland cement, - The moisture buffer value measured 10 days or more after manufacturing is 0.75 or higher. Prefabricated elements.

12. A method (100) for producing prefabricated elements prepared from a building binder, wherein the building binder comprises a raw clay matrix, an alkaline activating composition, a calcined metal oxide composition, and an anti-flocculating agent, and the method (100) is - A building binder is provided comprising at least 40% by weight of a raw clay matrix containing at least one raw clay from the smectite family, an anti-flocculation agent, at least 20% by weight of a calcined metal oxide composition, and an alkaline activating composition (110), wherein the building binder contains 10% to 30% by dry weight of the alkaline activating composition, the at least one raw clay from the smectite family corresponds to at least 20% by weight of the building binder, and the building binder contains less than 15% by weight of Portland cement; - Mix the building binder with granules and water (120); and - A curing step (130) of the mixture is carried out, which includes heat-treating the mixture at a temperature of 100°C or lower for a period of 2 to 23 hours. Method (100), comprising: the anti-flocculation agent being an organic compound selected from lignosulfonates, polyacrylates, humates, or mixtures thereof; the alkaline activating composition comprising sulfates, hydroxides, carbonates, lactates, organic phosphates, or combinations thereof; and the calcined metal oxide composition being selected from blast furnace slag and pozzolanes selected from volcanic ash, fly ash, silica fume, and metakaolin.

13. A method (100) for producing a prefabricated element according to claim 12, characterized in that the raw material clay matrix contains a mixture of at least two types of clay.

14. The raw material clay matrix is ​​at least 100 m 2 A method (100) for manufacturing a prefabricated element according to claim 12 or 13, characterized by comprising at least one clay having a specific surface area equal to / g.

15. A method (100) for manufacturing a prefabricated element according to claim 12, characterized in that the mass ratio of the raw clay matrix to the fired metal oxide composition in the building binder is 1:1 or more.

16. A method (100) for producing a prefabricated element according to any one of claims 12 to 15, characterized in that the building binder contains up to 25% by dry weight of the alkaline activating composition.

Citation Information

Patent Citations

  • Modifier for bentonite

    JP1991024146A

  • Production of moisture-adjustable building material by paper making method and moisture-adjustable building material

    JP2000202815A

  • Humidity controlling construction material

    JP2001328857A

  • Building material having humidity conditioning properties and gas adsorbing / Decomposing properties

    JP2002235382A

  • Cavity filler

    JP2007077392A